Drug-Therapy Problems and Predictors among Hospitalized Heart-Failure Patients: A Prospective Observational Study - Fentie Wendie, Teklehaimanot; Tarekegn Angamo, Mulugeta (Drug, healthcare and patient safety, 2020)
Heart-failure patients are at high risk of experiencing drug-therapy problems, owing to polypharmacy, comorbidities, and usually advanced age. Drug-therapy problems can lead to poor clinical outcomes, increased health-care costs and decreased quality of life, and thus strategies for identifying, resolving, and preventing them are urgently needed. Therefore, this study aimed at investigating the incidence and predictors of drug-therapy problems among hospitalized heart-failure patients. This hospital-based prospective observational study was conducted from February 1 to May 31, 2014 at Jimma University Specialized Hospital. Patients of either sex aged 18 years and above with chronic heart failure and complete medical records were enrolled. Patients with high-output heart failure, <1 day of hospital stay, unwilling to give written informed consent, and unconscious without caregivers were excluded. Data were collected from medication charts, laboratory reports, patients/caregivers, morning multidisciplinary meetings, and ward rounds. Multivariate binary logistic regression analysis was done to identify independent predictors of drug-therapy problems. A total of 104 heart-failure patients (mean age 51.20±15.66 years, females 51.9%) were consecutively enrolled, and 95 (91.3%) had experienced at least one drug-therapy problem (total 268, mean 2.82±1.39 encounters per patient). Of these problems, 45.5% were the need for additional drugs, followed by noncompliance (22.0%), inappropriate dosing (9.3%), unnecessary drugs (9.0%), ineffective drugs (8.2%), and adverse drug reactions (6.0%). None of the independent variables was found to be an independent predictor of having at least one drug-therapy problem. However, the number of clinical/pharmacological risk factors (AOR 7.93), female sex (AOR 3.24), and length of hospital stay (AOR 12.98) were predictors of noncompliance. Patients suffered from a large number of drug-therapy problems. Drugs with survival benefit were underused. Noncompliance and the need for additional drug therapy were the most frequently identified drug-therapy problems. Numbers of clinical/pharmacological risk factors, length of hospital stay, and female sex were identified as predictors for noncompliance.